Quantitative and empirical analysis of nonlinear dynamic macromodels - Carl Chiarella; Reiner Franke; Peter Flaschel; Willi Semmler (Emerald, 2006)
This book represents an ongoing research agenda the aim of which is to contribute to the Keynesian paradigm in macroeconomics. A currently dominant research strategy in macroeconomics is based on the Dynamic General Equilibrium (DGE) model. Its essential features are the assumption of intertemporal optimizing behavior of economic agents, competitive markets and price mediated market clearing through flexible wages and prices. Contributions to Economic Analysis was established in 1952. The series purpose is to stimulate the international exchange of scientific information. The series includes books from all areas of macroeconomics and microeconomics.
Includes index.
Keywords: Macroeconomics.; elektronické knihy; electronic books